The study of the Urban Heat Island effect in Cyprus using Google Earth Engine for 2013-2023 - Soteriades, Charalampos; Neophytides, Stelios; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2024)
The process of urbanization in Cyprus has been rapidly enhancing in the last 35 years, affecting the local climate. The contrast between energy absorption in developed urban areas and surrounding rural areas results in a differentiation of the local climate. The monitoring, therefore, of the urban heat island effect in main urban areas is essential, as data from a systematic examination can be of vital importance to policy makers and can assist them in adopting appropriate mitigation strategies and improve overall urban planning. The current study presents the results of the Urban Heat Island effect on the main cities in Cyprus (Paphos, Limassol, Larnaca and Nicosia) using Remote Sensing through Google Earth Engine. Data analytics techniques identify the correlation between different satellite indices and the Urban Heat Island phenomenon. The percentage of green coverage and the density of buildings have been identified as the main cause of the phenomenon. Findings from the study can be of use to local authorities to support their proposed revisions of local planning.
Keywords: Remote Sensing; urban heat island; vegetation cover; urban areas; correlation